LOCAL WISDOM OF THE PARSIDANGAN STONE LEGEND AT HUTA SIALLAGAN SAMOSIR: A LITERARY TOURISM PERSPECTIVE - Rabiatul Adawiyah Siregar; Ikhwanuddin Nasution; Pardi Pardi (Universitas Islam Sumatera Utara (UISU), 2022)
Local wisdom can be used as a medium for introducing culture to increase tourism. The purpose of this research is to describe about the transfer process of the legend of Parsidangan stone in Huta Siallagan, Samosir Regency in literary tourism perspective. The structure of the story then describes the local wisdom of the Parsidangan stone legend. Tourists' perceptions of the legend is very important to develop the potential of the locality, especially in tourism development. This qualitative research uses a descriptive inferential technique with a literary tourism perspective. Data were collected by observation and interview methods. The results show that there is a transfer of the Parsidangan stone legend from oral (spoken) to written (script) and animated films, which describe the structure of the story such as the theme of the Parsidangan stone folklore, namely the rocking chair as a meeting place and trial of King Siallagan. It is said that the Batak tribe has a tradition of keeping everything that will be done together, such as traditional parties, village parties, weddings, and funerals. The main character in this legend is King Siallagan. The background in this research is parsidangan stone, execution stone, fields, lakes. The plot in this legend is a mixed plot. The forms of local wisdom in the Parsidangan stone legend are hard work, justice, courtesy, commitment, discipline, and preservation.